Hidrolisado proteico misto de subprodutos de aves e fígado suíno em dietas para alevinos de tilápia do Nilo (Oreochromis niloticus) - Carvalho, Kerolay Valadão (2019)
This research aimed to evaluated diets containing different levels of inclusion of mixed protein hydrolysate of poultry and swine by-products (MPH) in feed of fingerlings of Nile tilapia (Oreochromis niloticus). Were used 336 fingerlings of tilapia of Nile (initial average weight 1,41±0,01g), distributed in 28 boxes of 70 liters with four replicates by treatment. The experimental design was entirely randomized and conducted by 28 days. Seven diets isoproteic and isoenergetic were evaluated, being one of them free of hydrolysate and fish meal (negative control), a second hydrolysate-free and containing fish meal (positive control), and other five diets with inclusion of 1, 2, 3, 4, 5 (%) of mixed protein hydrolysate. The results were submitted to homogeneity test of Levene, followed by Kruskal-Wallis for non-homogeneous averages and one-way (ANOVA) for Tukey test (P>0,05) for homogeneous means. Diets with inclusion of mixed protein hydrolysate for fingerlings of Nile tilapia in early stages for performance exhibited final mean length values more for the treatments with inclusion of hydrolysate and significant for inclusion of 1%, hepatossomatic indexes, visceral fat and nutrient utilization efficiency there were didn’t significance effects (P≥0,05). The histomorphometric of intestine demonstrated that hydrolysate might be related to maintaining the health of intestinal tissue, consequently, can be linked to morphometric aspects of hepatocyte nucleus, suggesting higher metabolic levels for treatments with inclusion of 3%, that exhibited values of perimeter, area, and volume nuclear significantly higher than the negative control treatments as well as for the positive control and 1% with the exception of the nuclear volume variable, with values significantly higher for 3% and 5% in relation to the negative control. The analysis of vacuolization of liver tissue demonstrated that the treatment positive control showed normal liver tissue, so that inclusions of 3 and 5% were normal or little vacuolated vacuolization condition. For the centesimal composition of the carcass was verified higher deposition mineral matter for the treatment 5%. It is suggested to include mixed protein hydrolysates at levels of 3% inclusion in the diet for Nile tilapia fingerlings as an alternative to the use of fish meal with protein ingredients of vegetal origin to maintain the morphofunctional conditions of the intestine and liver tissue.